Survey of Mortality Due to Influenza A in North of Iran, 2015-2016 - Babamahmoodi, Farhang; Haghshenas, Mohammadreza; Ahangarkani, Fatemeh; Davoudi, Alireza; Ashkezari, Elham A.; Davoodi, Lotfollah (Current Respiratory Medicine Reviews, 2017)
Background and Aims: In late November 2015 and early February 2016, an outbreak of H1N1 influenza A virus infection occurred in the north of Iran. The aim of this study was to describe the incidence of mortality due to H1N1 influenza among patients admitted in hospitals affiliated to Mazandaran University of Medical Sciences in north of Iran. Material and Methods: A descriptive cross-sectional study was done using the medical records of mortality cases of influenza A, whose result of RT-PCR (reverse transcriptase polymerase chain reaction assay) confirmed H1N1. Demographic data, symptoms and signs of disease, clinical backgrounds, radiographic evidences, laboratory findings, treatment procedure and outcome of these patients were recorded. Results: Out of the 428 confirmed cases of influenza A (H1N1) in Mazandaran province between 21st March 2015 and 19th March 2016, 23 (5.3%) deaths (10 males and 13 females) were reported. Death occurred between outbreak in late November 2015 and early February 2016. The average age of deceased patients was 46.9±21.4 years old (range 14-95 years). The most prevalent symptoms and signs were: fever (91.3%), cough (82.6%), dyspnea (73.9%), and headache (69.5%). The most underlying conditions among decedent patients were: heart failure (47.8%), diabetes mellitus (30.4%), and BMI≥40 (30.4%). Conclusion: The association between underlying risk factors and mortality rate, emphasizes the priority of vaccination in high risk groups.
Keywords: survey